(untitled) (Philological Studies, 2019)
Radomir’s Evangeliary’s richest illuminated Macedonian manuscript from the 13th century and according to the motive of ornamentation belongs in the group of manuscripts with teratological (monster) style, which is a specific composition made of strips and twigs which are each intertwined with monster forms of wild animals and birds, whose spokes merge into strips, masterfully delineated so that it is not known where the figure ends and where tapes start. The ornament are headpieces and decorative additions, and the initials, total of 314, are in the teratological, interlaced and few in the vegetal style.